Relative income inequality and selected health outcomes in urban Chinese youth - Sun, Ping (2011)
Self reported cross-sectional data gathered in 2002 from 12,449 middle and high school students from seven major cities in China were examined to explore the association of self-perceived relative income inequality (SPRII) with general health status, depression, stress, and cigarette smoking. Two types of self-perceived relative income were evaluated: household income relative to peers (SPRII-S) and relative to their own past (SPRII-P). SPRII-S and SPRII-P were coded as three-level categorical variables: lower, equal, and higher. As hypothesized, the youth in the “Lower” SPRII-S or SPRII-P groups reported the worst general health and the highest levels of depression and stress; the youth in the “Higher” groups reported the best general health. Unexpectedly, the youth in the “Higher” groups did not report the lowest levels of depression and stress, and the relationship between SPRII and cigarette smoking was even less straightforward. The expected positive relationship between SPRII and the general health status is consistent with previous research, but the relationships between SPRII and depression, stress, and cigarette smoking behavior are not. Further studies are needed to elucidate the complex associations between SPRII and health outcomes in rapidly transforming economies such as China.